Anti-Inflammatory Activity of a Selection of Antidepressant Drugs: Kaempferol 3-O-glycoside from Tribulus terrestris L. - Valiollah Hajhashemi; Mohsen Minaiyan; Mahdieh Eftekhari (Iranian Journal of Pharmaceutical Sciences, 2008)
Anti-inflammatory activity has been reported for a few of antidepressant drugs and in contrary sertraline has potentiated inflammation. In this study, anti-inflammatory effect of a collection of antidepressant drugs belonging to different classes was evaluated to help a rational selection of these drugs in disease conditions such as association of depression or anxiety with inflammatory diseases such as rheumatoid arthritis. Male Wistar rats weighing 160-200 g were used. Anti-inflammatory activity was assessed using carrageenan-induced paw edema test.Amitriptyline, nortriptyline, desipramine, trimipramine, fluvoxamine (37.5 and 75mg/kg), fluoxetine (30 and 60 mg/kg), citalopram (10 and 40 mg/kg), doxepin and maprotiline (25 and 50 mg/kg) were administered s.c. 30 min. prior to subplantar injection of 100 µl carrageenan suspension (1% w/v). Difference of paw volume measured just before and 4 h after carrageenan injection was considered as an index of inflammation. Except nortriptyline and citalopram, all tested drugs showed anti-inflammatory activity. It seems that the anti-inflammatory effect is not correlated with inhibition of norepinephrine and/or serotonin reuptake transporters and further studies are needed to clarify the exact mechanism of their anti-inflammatory action.